2008
DOI: 10.1016/j.hrthm.2008.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic effects of ranolazine in canine pulmonary vein sleeve preparations

Abstract: Objectives-To determine the electrophysiologic effects of ranolazine in canine pulmonary veins (PV) sleeve preparations.Background-Ectopic activity arising from the PV plays a prominent role in the development of atrial fibrillation (AF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(121 citation statements)
references
References 28 publications
11
110
0
Order By: Relevance
“…Previous studies have shown that DAD-and latephase EAD-induced TA can be easily induced in canine PV sleeve preparations after the addition of isoproterenol, ACh, and high calcium alone or in combination (Patterson et al, 2005(Patterson et al, , 2006Sicouri et al, 2008aSicouri et al, , 2009, in canine-and rabbitisolated single PV myocytes (Chen et al, 2000;Chen and Chen, 2006) and in canine coronary perfused right atrial preparations Antzelevitch, 2003, 2006). Conditions permitting intracellular calcium loading facilitate the development of DADs and late phase 3 EADs (Burashnikov and Antzelevitch, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that DAD-and latephase EAD-induced TA can be easily induced in canine PV sleeve preparations after the addition of isoproterenol, ACh, and high calcium alone or in combination (Patterson et al, 2005(Patterson et al, , 2006Sicouri et al, 2008aSicouri et al, , 2009, in canine-and rabbitisolated single PV myocytes (Chen et al, 2000;Chen and Chen, 2006) and in canine coronary perfused right atrial preparations Antzelevitch, 2003, 2006). Conditions permitting intracellular calcium loading facilitate the development of DADs and late phase 3 EADs (Burashnikov and Antzelevitch, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Isolated myocytes and dynamic-clamp experiments have shown that an isolated increase of either of these two late inward currents promotes cellular early and delayed afterdepolarizations (EADs and DADs respectively) causing rapid triggered activity [16,17]. Indeed inhibition of the I Na-L with the highly potent (IC 50 =0.143 μM) and selective inhibitor GS-967 [18] suppresses EADs in isolated atrial myocytes [18,19]. The purpose of this study is to test the following two hypotheses; 1) oxidative stress-mediated activation of CaMKII signaling with hydrogen peroxide (H 2 O 2 ) in structurally remodeled atria characterized with increased atrial tissue fibrosis promotes AF by the mechanism of EAD and DAD-mediated triggered activity; and 2) selective inhibition of the enzymatic activity of CaMKII or its distal target, the I Na-L with the specific I Na-L blocker, GS-967, [18] suppresses the oxidative AF.…”
Section: Introductionmentioning
confidence: 99%
“…22 Another study tested ranolazine with dronedarone in treatment of AF in animal models and found that the combined use results in better rhythm control. 23 Moreover, ranolazine helped with dronedarone to decrease ischemia-induced vulnerability to AF as well as ventricular arrhythmias.…”
Section: Ranolazine In the Management Of Atrial Fibrillation Experimementioning
confidence: 99%